Advances in engineering and optimization of transcription factor-based biosensors for plug-and-play small molecule detection. (August 2022) - Pham, Chester; Stogios, Peter J.; Savchenko, Alexei; Mahadevan, Radhakrishnan
Abstract : Transcription factor (TF)‐based biosensors have been applied in biotechnology for a variety of functions, including protein engineering, dynamic control, environmental detection, and point-of-care diagnostics. Such biosensors are promising analytical tools due to their wide range of detectable ligands and modular nature. However, designing biosensors tailored for applications of interest with the desired performance parameters, including ligand specificity, remains challenging. Biosensors often require significant engineering and tuning to meet desired specificity, sensitivity, dynamic range, and operating range parameters. Another limitation is the orthogonality of biosensors across hosts, given the role of the cellular context. Here, we describe recent advances and examples in the engineering and optimization of TF-based biosensors for plug-and-play small molecule detection. We highlight novel developments in TF discovery and biosensor design, TF specificity engineering, and biosensor tuning, with emphasis on emerging computational methods. Highlights: Transcription factor-based biosensors are powerful analytical synthetic biology tools. Biosensors can be used for detection, metabolic engineering, and protein engineering. Performance characteristics of biosensors need to be tuned for application. A variety of methods exist to discover, engineer, and tune biosensors. Advances in computational and high-throughput methods improve biosensor engineering.